1980
DOI: 10.1161/01.str.11.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Positron imaging of cerebral blood flow during continuous inhalation of C15O2.

Abstract: SUMMARY This investigation tests the hypothesis that the normal cerebral image obtained non-invasively during continuous inhalation of C"O, is related to cerebral blood flow. Trace amounts of CO, labeled with the positron-emitting radionuclide " 0 were administered to 4 normal subjects at normo-and hypocapnia and to 2 of these subjects at hypercapnia. Hypocapnia typically caused a marked decrease in cerebral " 0 activity, and hypercapnia a small increase in activity. The relative difference in the change in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The outcome of such areas was universally poor, exhibiting necrosis on late structural imaging [17][18][19][20][21][22][23]. Postischemic hyperperfusion has also been documented in various animal studies [18][19][20][21][22][23]. Yonas et al [24] showed that 20 min of vascular occlusion in baboons resulted in a brief episode of hyperperfusion with no subsequent alteration seen on CT and only minimal random neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of such areas was universally poor, exhibiting necrosis on late structural imaging [17][18][19][20][21][22][23]. Postischemic hyperperfusion has also been documented in various animal studies [18][19][20][21][22][23]. Yonas et al [24] showed that 20 min of vascular occlusion in baboons resulted in a brief episode of hyperperfusion with no subsequent alteration seen on CT and only minimal random neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
“…OEF and CM R02 using the ECAT system were relatively unsatisfactory [6] and conflicted with results obtained by others using a differ ent PET system [3]. This raised questions concerning the validity of the 'sO continuous inhalation model, for which only indirect evi dence was available [2], However, a better understanding of the above-mentioned tech nological difficulties led to designing an ex perimental study in baboons, using the wellknown relationship between CBF and PaCOj, that clearly demonstrated that C150 2 continuous inhalation allows tomographic measurement of CBF [9], During the course of this study, a point was raised concerning the consequences of the nonlinearity of the tissue H2i50-CBF relationship. In this regard, the inescapable admixture of two compo nents with different blood flows and water partition coefficients -namely, gray and white matter whatever the size and loca tion of the region under consideration, results in systematic underestimation of the com puted CBF by as much as 25%.…”
Section: Pet Absolute Quantitation Of Cbf Oef and C M R 02mentioning
confidence: 99%
“…PET uses positron‐emitting radioisotope‐labeled molecular probes such as 18 F‐fluoromisonidazole ( 18 F‐MISO) (12–14) or 64 Cu‐diacetyl‐bis( N 4 ‐methylthiosemicarbazone) ( 64 Cu‐ATSM) (15–17), which have high affinity for the hypoxic atmosphere and obtain spatial maps of hypoxic regions in a patient and/or experimental animals. Measurement of oxygen metabolism was clinically carried out by PET using 15 O gas as the probe (18–22). SPECT is also a radiological imaging technique which has been used for measurement of blood perfusion volume in the brain employing a γ‐ray emitting radioisotope such as N ‐isopropyl‐ p ‐[ 123 I]iodoamphetamine ( 123 I‐IMP) (23–28), [ 99m Tc]‐hexamethylpropyleneamine oxime ( 99m Tc‐HMPAO) (29), or [ 99m Tc]‐ethyl cysteinate dimer ( 99m Tc‐ECD) (30–32).…”
mentioning
confidence: 99%